AB0596 The immune complexes of igg/igm bound to b-2-glycoprotein i are associated with livedo reticularis, thrombocytopenia and sicca in aps patients. (12th June 2018) - Pérez, D.; Stojanovich, L.; Naranjo, L.; Stanisavljevic, N.; Bogdanovic, G.; Serrano, M.; Serrano, A.
Abstract : Background: Several manifestations strongly associated with APS have been excluded as classification criteria. 1 2 Objectives: The aim of this study was to investigate correlation between circulating immune-complexes of IgG or IgM antibodies bound to B2GPI (B2G-CIC and B2M-CIC) and clinical manifestations in Serbian cohort of APS patients. Methods: A total of 57 patients with APS were evaluated: 35 with PAPS and 22 patients with SAPS. Mean age was 47.6±1.6 years; 36 (63.2%) were women. All patients have met the 2006 revised Sydney criteria for APSQuantification of B2G-CIC and B2M-CIC levels was performed as previously, for detect B2G-CIC was used anti-human IgG HRP-conjugate and for B2M-CIC human IgM HRP- conjugate, both from INOVA (INOVA Diagnostics Inc., San Diego, CA, USA). Results: In our cohort Serbian APS patients the prevalence of CIC was 19.29% (11/57); 8 patients with B2M-CIC and the remain 3 patients with B2G-CIC. Livedo reticularis was diagnosed with higher prevalence in patients with CIC compared with patients without CIC; 63.6% and 23.9%, respectively (OR: 5.57, p=0.01). In patients with CIC, thrombocytopenia and leukopenia were more prominent; 54.4% vs 17.4% (OR: 5.70, p=0.01) and 45.5% vs 13.0% (OR: 5.56, p=0.01), respectively. Ophthalmic sicca was more prevalent in patients with CIC; 54.4% vs 8.7% (OR: 12.6, p<0.001). Although complement consumption was more frequent in patients with CIC (figure 1). Figure 1 Mean levels of C3 (A) and C4 (B) complement in groups. Mean levels of C3 (115.6±9.2 mg/dL and 140.9±4.3 mg/dL, group-1 and group-2 respectively) and mean levels of C4 (140.9±4.3 mg/dL and 30.8±1.6 mg/dL, group-1 and group-2, respectively). Conclusions: B2G-CIC and B2M-CIC are strongly associated with clinical manifestations related to APS. Widening the APS spectrum is indispensable to better understand this syndrome. References: [1] Stojanovich L, Kontic M, Djokovic A, Marisavljevic D, Ilijevski N, Stanisavljevic N, et al. Association between systemic non-criteria APS manifestations and antibody type and level: results from the Serbian national cohort study. Clin Exp Rheumatol. 2013 Mar-Apr;31(2):234–42. [2] Stojanovich L, Markovic O, Marisavljevic D, Elezovic I, Ilijevski N, Stanisavljevic N. Influence of antiphospholipid antibody levels and type on thrombotic manifestations: results from the Serbian National Cohort Study. Lupus. 2012Mar;21(3):338–45. Acknowledgements: This work was supported by research grant number 175041, and TR 32040 for 2011–2018, issued by the Ministry of Science of the Republic of Serbia. Disclosure of Interest: None declared